Fault Level Considerations in Tomorrow's Wind and PV-Rich Power Grids: A Review - Aljarrah, Rafat; Karimi, Mazaher; Marzooghi, Hesamoddin (IEEE, 2026)
The increased penetration of Renewable Energy Sources (RESs), such as Photovoltaic (PV) and wind energy, in transmission and distribution networks is changing the features of current and future power systems. RESs may alter the characteristics of power systems due to their different dynamic behavior and limitations compared to centralized conventional Synchronous Generators (SGs). This is mainly attributed to Power Electronics (PE) interfaces (i.e., converters) utilized for integration with the power grid. As PE-based RESs exhibit lower and significantly different fault current contributions than SGs, fault level reduction is considered a major challenge for future power systems. Besides, such RESs may introduce new dynamics into the short-circuit (SC) current characteristics of power systems, which, in turn, may pose challenges to the strength, stability, operation, and protection of the grids. To tackle such challenges, it is essential to better understand the SC characteristics of the different RESs, specifically Wind and PV systems. In addition, evaluating their impact on the system fault level is necessary, especially in future power scenarios where most of the power is expected to be met by RESs. Hence, this study provides a comprehensive review of the contributions of SC currents from RESs to SC dynamics and the system fault level, addressing key challenges and gaps in the literature for researchers and utility engineers.
Keywords: photovoltaic; reduced fault level; renewable-rich power systems; renewable’s fault contributions; system strength; wind energy; fi=Sähkötekniikka|en=Electrical Engineering|